Investigating the Relationship between the Use of Reading Assistant Software and Reading Comprehension Skills: A Case among Thai EFL University Students - Kitjaroonchai, Nakhon; Sanitchai, Pimolporn; Phutikettrkit, Chomphunut (JET (Journal of English Teaching), 2024)
This study examined the relationships between reading assistant (RA) software usage, reading comprehension ability, and post-TOEIC reading scores among Thai EFL university students. Seventy-six students from a private international university in central Thailand participated. Data were collected from students’ pre- and post-TOEIC reading scores and their RA software usage over twelve weeks. Pearson’s r was used to analyze the connections between various variables: weekly duration spent on RA software, count of chosen reading passages, reading level identified by the RA software, fluency and accuracy levels per minute, percentage-based reading comprehension score, and pre- and post-TOEIC reading scores. The findings revealed some correlations among variables such as time invested in RA software, reading level, fluency and accuracy rates per minute, and reading comprehension scores. However, there was no significant correlation between the frequency of RA software use and students’ post-TOEIC reading scores. This suggests that using RA software may not directly impact learners’ reading comprehension skills. The study implies that while certain language learning tools may be beneficial, they might not substantially enhance language proficiency as measured by standardized tests like the TOEIC reading comprehension skills. Some implications for improving EFL students' reading comprehension skills through RA software are briefly discussed.